Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages 5 and bad living conditions during these vital years. 52.5 per cent. of the working class children of York under one year of age were living in poverty in 1936. Taking these figures as typical of the country as a whole, it is probable that more than half the working class of this country have spent some part of their childhood in poverty. Mr. Rowntree further estimated that 89 per cent. of the children would be in poverty for more than 5 years, and 66 per cent. for ten years or more.* 2 — INFERIOR EDUCATION. (1) The Class System in Education. The differences — social and economic — which divide the nation into distinct classes are perpetuated by the system of education. Here are typical examples of the education received by boys of the same average degree of intelligence, but drawn from four different social classes. Type of Education Cost. Age. UPPER CLASS. 5-8 Kindergarten. 3 years at £15 £45 8—13 Private preparatory boarding school. 6 years at £120 ....... £600 13—18 Public School. 5 years at £180 £900 18—21 Oxford or Cambridge. 3 years at £200† £800 i.e., 16 years' education for £2,345 Age. UPPER MIDDLE CLASS. 5-11 Private school or grammar school. 6 years at £13 £78 11—18 Secondary School. 7 years at £11 £77 18—21 Provincial University. 3 years at £80† £240 i.e., 16 years education for £395 Age. LOWER MIDDLE CLASS. 5—11 Elementary School £0 11—16 Secondary School. 5 years at £11 £55 i.e., 11 years' education for £55 Age. WORKING CLASS. 5—14 Elementary School. i.e., 9 years' education free. £0 Differences in Quality. Not only is education the briefer as one descends the social scale, but it is also of inferior quality. Elementary schools are often housed in obsolete buildings, with dark classrooms, inadequate sanitary arrangements, and a depressing asphalt yard for playground. 753 condemned schools are still in use and of these 541 are church schools. Secondary schools are much better ; but they cannot be compared with the "public schools," standing in their acres of beautiful grounds. * Poverty and Progress, Ch. VI † Including residence in term-time only (24 weeks in the year). 15X/2/98/13